Políticas públicas de educação ambiental e processos de mediação em escolas de Ensino Fundamental - Arnaldo, Maria Aparecida; Santana, Luiz Carlos (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (Unesp), Faculdade de Ciências, campus de Bauru., 2018)
Abstract: This article sees the school as a space for mediation in public policies for environmental education and the processes by which this mediation takes place. After the questionnaires, we selected seven elementary schools of a city in São Paulo state, which were investigated through interviews, observation and document analysis. The results showed that by: involving crosscutting, interdisciplinary and project work in the development of environmental education; understanding environmental education as a possibility of awareness of the subjects on environmental issues; considering students as multipliers of knowledge about environmental issues and; integrating the community using the environmental theme, the investigated schools developed processes where the mediations of public environmental education policies are manifested. It was noted, however, that such processes, predominantly showing, pragmatic conceptions of environmental education, lead several times, to beliefs in changes in the structures of society.

Resumo: Este artigo analisa a escola como espaço de mediação das políticas públicas de educação ambiental e os processos pelos quais essa mediação ocorre. A partir de questionários, foram selecionadas sete escolas de Ensino Fundamental I de um município paulista, investigadas por meio de entrevistas, observações e análises de documentos. Os resultados apontaram que as escolas investigadas desenvolvem processos em que as mediações das políticas públicas de educação ambiental são manifestadas ao: envolver a transversalidade, a interdisciplinaridade e o trabalho com projetos no desenvolvimento da educação ambiental; compreender a educação ambiental como possibilidade de conscientização dos sujeitos sobre questões ambientais; considerar os alunos como multiplicadores dos conhecimentos sobre as questões ambientais; procurar integrar a comunidade utilizando a temática ambiental. Entretanto, observou-se que esses processos são permeados, predominantemente, por concepções pragmáticas de educação ambiental, que deixam, muitas vezes, de vislumbrar transformações nas estruturas da sociedade.
Public policies for an Environmental Education and mediation processes in elementary schools
Keywords: Environmental education; Public policy; Mediation; Public school; Educação ambiental; Políticas públicas; Mediação; Ensino fundamental